Comparative study on galacturonic acid and its antioxidant activity of pectin from fruit waste peels - Duangkamol, Chuthamat; Phapattamas, Khemmanat; Burikan, Parichat; Nisakorn, Siripakr; Akesakrulsab, Yosita; Kongtawee , Kanokrada; Manojai, Natthaporn (SciTech Research Journal, 2025)
The objective of this research is to compare the galacturonic acid and antioxidant activity of pectin extracted from five waste fruit peels: pomelo, pomegranate, lemon, guava, and passion fruit. The pectin from the fruit peels was obtained by acid hydrolysis and then precipitated with 99% ethanol. Pectin from passion fruit peel had the highest levels of galacturonic acid, followed by guava, pomegranate, pomelo, and lemon, respectively. The galacturonic acid of pectin was determined, and the antioxidant activity was studied using 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay. According to the research, pectin from pomegranate peel has the highest antioxidant activity at all concentrations. These research findings not only enhance the value of waste fruit peels but also have the potential to be utilized in the food, medical, and pharmaceutical industries.